PENGARUH PEMBERIAN KOMPOS DENGAN BERBAGAI BIOSTARTER TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SEMANGKA (Citrullus vulgaris L): THE EFFECT OF COMPOSTING WITH VARIOUS BIOSTARTERS ON THE GROWTH AND PRODUCTION OF WATERMONE (Citrullus vulgaris L) - I Nengah Ardiana; Hertasning Yatim; Lani Pelia; Sofyanto hapari (Fakultas Pertanian Universitas Tompotika Luwuk, 2022)
Lack of availability of nutrients in the soil is one of the factors that affect the production of watermelon plants. Therefore, this study aims to determine the effect of the best types of compost from various biostarters on the growth and yield of watermelon plants. The research was carried out on agricultural land in Bumi Beringin Village, Luwuk Utara District, Banggai Regency, this research was carried out in July using the experimental method (experiment). The treatment factor was a single factor, namely rice husk compost, which consisted of 5 levels of treatment. The experimental units were arranged in a Randomized Block Design (RAK) with 3 replications, so that the number of experimental units of harmony was 15 units. The treatments were combined with rice husks in the form of Trichoderma, EM4, Stardec, and Starbio with each dose of 640 g/hole. The results showed a very significant effect on the variable length of plant observation at week 2 of WAP with the best results in the treatment of P2 = Compost Fertilizer (Em 4) 640 gr/hole with an average of 13.89 cm. Significant effect on the number of leaves at week 2 of MST with the best results in the treatment of P2 = Compost Fertilizer (Em 4) 640 g/hole with an average of 6.89. The number of fruits had a significant effect with the best treatment at P2 (Compost Fertilizer (Em 4) 640 gr/hole) with an average of 4.67. And the fruit circumference observation had a very significant effect with the best treatment at P4 (Compos Fertilizer (Starbio) 640 gr/hole) with an average of 67.88 cm. And for the weight of the planting fruit the best and significant effect on the P2 treatment (Compost Fertilizer (Em 4) 640 gr/hole) with an average of 9.10 cm.